A STUDY ON THE PREVALENCE OF SYMPTOMS OF ENDOMETRIOSIS IN ADOLESCENT GIRLS VISITING A TERTIARY CARE CENTRE IN TAMIL NADU - Dr. Sravani Chithra Ch; Dr. Sampathkumari S; Suhashini Karnal C; Dr. Sri Varshitha D; Dr. Krishna Prasanth Baalann (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: The existence of endometrial glands and stroma outside the uterine lining is the hallmark of endometriosis. The incidence of endometriosis in teenagers ranges from 19% to 73%. Nevertheless, it is still unclear how common the illness actually is among adolescents in general. In our study, adolescents who exhibit symptoms suggestive of endometriosis or who are at risk of developing the condition were identified by a questionnaire. Methodology: This six-month, single-center study was carried out in a tertiary care hospital’s Obstetrics and Gynecology department. A validated questionnaire, prepared after reading the literature and selecting risk factors, symptoms, and phenotypic aspects of endometriosis, was given to each participant of the 240 teenage females who were enrolled in the study. Results: It was found from analysis of the responses to the questionnaire that out of 240 adolescents, majority of the adolescents belonged to 15-16 years of age (53.8%) and 52.1% had a normal BMI. A significant proportion (35.8%) had periods lasting more than 5 days. 38.8% of adolescents experienced pain. The most common symptom seen was diarrhea (23.3%) followed by constipation or painful bowel movements (22.9%). About 19.2% of the participants reported experiencing flatulence, gastritis or vomiting and 18.3% reported painful or difficult urination. Increased frequency of urination was seen in 19.2% of the adolescents and 11.3% of the participants reported incomplete emptying of the bladder. Conclusion: In conclusion, because teenage endometriosis presents in a variety of ways, diagnosis can be challenging. Adolescents at risk of endometriosis can be promptly evaluated with the use of an endometriosis screening questionnaire, which could be a valuable tool for both physicians and self-screening.